2018
DOI: 10.1007/s41669-018-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

High Healthcare Resource Use in Hospitalized Patients with a Diagnosis of Spinal Muscular Atrophy Type 1 (SMA1): Retrospective Analysis of the Kids’ Inpatient Database (KID)

Abstract: The average total charges for a single SMA1 admission were higher than those of the no CCC group. Because most infants with SMA1 require multiple hospitalizations per year, previous estimates may dramatically underestimate the direct costs associated with HRU. Further studies are required to determine the indirect costs and societal impacts of SMA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…In accordance with findings from the current study, previous studies have consistently found SMA to be associated with high HRU and healthcare costs [11][12][13][14][15][16][17][18][19] , including a few recent claims-based studies that evaluated the economic burden of SMA [12][13][14] . For example, Dabbous et al 13 conducted a retrospective analysis of patients with SMA1 using the Quintiles IMS's PharMetrics Plus Health Plan Claims Database (February 2011-November 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In accordance with findings from the current study, previous studies have consistently found SMA to be associated with high HRU and healthcare costs [11][12][13][14][15][16][17][18][19] , including a few recent claims-based studies that evaluated the economic burden of SMA [12][13][14] . For example, Dabbous et al 13 conducted a retrospective analysis of patients with SMA1 using the Quintiles IMS's PharMetrics Plus Health Plan Claims Database (February 2011-November 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Assessments of the real-world economic burden of SMA, including the healthcare resource utilization (HRU) and healthcare costs associated with the disease, remain limited in the US [11][12][13][14][15][16][17][18][19] . In a study conducted by Dabbous et al 13 , which evaluated the economic burden of patients with SMA1 in the US, healthcare costs in the first month following SMA diagnosis averaged $27,063 per patient compared to $274 among matched patients without SMA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved functioning in SMA patients may also have positive economic effects. Our recent retrospective analysis of the Kids’ Inpatient Database (KID) database showed that the admission charges for SMA1 children were an average of $150 921 per hospitalization ($11 143 per day) . The decreased frequency of respiratory infections and hospitalizations observed following treatment with AVXS‐101 compared to untreated SMA1 patients, are likely to result in concomitant reductions in healthcare costs associated with treating SMA1 children.…”
Section: Discussionmentioning
confidence: 99%
“…(12) Multiple studies have found substantially higher costs for patients with SMA compared to healthy populations. (10,11,13) In addition to impairment on quality of life and social participation among patients with SMA, SMA was associated with reduced caregiver quality of life, which was related to patient burden, impaired psychosocial well-being, and loss of caregiver's productivity. (14)(15)(16) Despite the progress in SMA treatment with two important landmark treatments (approved by the Food and Drug Administration [FDA]), the disease burden and related unmet need remains signi cant for many patients with SMA and their caregivers.…”
Section: Introductionmentioning
confidence: 99%